Different conjugated system Zn(ii) Schiff base complexes: supramolecular structure, luminescent properties, and applications in the PMMA-doped hybrid materials. Issue 4 (9th January 2017) - Dong, Yu-Wei; Fan, Rui-Qing; Chen, Wei; Zhang, Hui-Jie; Song, Yang; Du, Xi; Wang, Ping; Wei, Li-Guo; Yang, Yu-Lin
Abstract : Five Zn(ii ) complexes with different conjugated systems were synthesized.Zn3 was incorporated into PMMA, creating a high performance material. Abstract : A series of Zn(ii ) complexes with different conjugated systems, [ZnL 1 Cl2 ]2 (Zn1 ), [ZnL 2 Cl2 ] (Zn2 ), [Zn(L 3 )2 ]·(ClO4 )2 (Zn3 ), [Zn2 L 4 Cl4 ] (Zn4 ), and [ZnL 5 Cl2 ] (Zn5 ), were synthesized and subsequently characterized via single crystal X-ray diffraction, 1 H and 13 C NMR, FT-IR, elemental analyses, melting point, and PXRD. The X-ray diffraction analyses revealed that the supramolecular frameworks of complexesZn1–Zn5 are constructed by C–H⋯O/Cl hydrogen bonds and π⋯π interactions. ComplexesZn1–Zn3 feature 3D 6-connected 4 12 ·6 3 topological structures, whereas complexZn4 exhibits a 3D 7-connected supramolecular framework with a 4 17 ·6 4 topological structure. However, complexZn5 shows one-dimensional "wave-like" chains. Based on these varied structures, the emission maximum wavelengths of complexesZn1–Zn5 can be tuned in a wide range of 461–592 nm due to the red shift direction of λ em caused by different conjugated systems and their electron donating abilities. ComplexZn3 shows a strong luminescence in the solid state and in the acetonitrile solution. Therefore, a series ofZn3 -poly(methylmethacrylate) (Zn3 -PMMA) hybrid materials were obtained by controlling the concentration of complexZn3 in poly(methylmethacrylate) (PMMA). At an optimal concentration of 4%, the doped polymer film ofZn3 -PMMA displays strong green luminescence emissions that are 19-fold in the luminescence intensities and 98 °C higher in the thermal stability temperature compared to theZn3 film.